Dual-action platinum(II) Schiff base complexes: Photocytotoxicity and cellular imaging. (1st November 2019) - Banerjee, Samya; Capper, Miles S.; Clarkson, Guy J.; Huang, Huaiyi; Sadler, Peter J.
Graphical abstract: Intense phosphorescence of a family of square-planar Schiff base Pt(II) complexes is used to map their distribution in cancer cells. Although non-toxic in the dark, they are potently toxic to cancer cells on green-light irradiation via generation of singlet oxygen, with potential to act as dual theranostic agents and photodynamic therapy sensitisers. Abstract: Nine photo-stable Pt(II) Schiff base complexes [Pt(O^N^N^O)] (Pt1 –Pt9 ) containing tetradentate salicylaldimine chelating ligands have been synthesized and characterized as potential photosensitisers for photodynamic therapy (PDT). The effects of electron-withdrawing versus electron-donating substituents on their electronic spectral properties are investigated. Pt1 –Pt9 show broad absorption bands between 400–600 nm, which makes them useful for green-light photodynamic therapy. The complexes showed intense phosphorescence with emission maxima at ca. 625 nm. This emission was used to track their cellular localization in cancer cells. Confocal cellular imaging showed that the complexes localized mostly in the cytoplasm. In the dark, the complexes were non-toxic to A549 human lung cancer cells, but exhibited high photo-toxicity upon low-dose green light (520 nm, 7.02 J/cm 2 ) irradiation via photo-induced singlet oxygen generation. Thus, these photoactive Pt(II) complexes have the potential to overcome the problem of drug resistance and side effects of current clinical Pt(II) drugs, and to act as both theranostic as well as therapeutic agents.